Kompetencje i zadania jednostek samorządu terytorialnego w zakresie bezpieczeństwa zdrowia ludności - Wojtczak, Krystyna (Studia Prawa Publicznego, 2018)
The creation of conditions aimed at ensuring the health of the population is a supreme value. Polish legal solutions make it a constitutional obligation of the State and local self-government. The current Constitution of the Republic of Poland of 2 April 1997 does not define the limits of this obligation; it only states that the conditions for ensuring everyone’s right to health protection and the scope of health services that are financed from public funds are to be specified by statute. In fact, the system leaves almost complete freedom in this area to the legislator. In the article the solutions adopted by local self-government units in 1991–2018 are evaluated. In order to fulfil certain competences and tasks imposed by law on the commune, poviat and self-governing regional bodies, the legislator has determined two spheres of their activity: (i) implementation of their own tasks in the field of health protection and health promotion, and (ii) establishment and running of entities which before 2011 were termed public health care facilities and after 2011 changed their name into medical entities which are not entrepreneurs. In neither of these spheres of activity is the participation of local government units identical. In the first sphere, the differences result from both the constitutional acts shaping their own tasks in the field of health protection, as well as health programmes which they adopt for their implementation. In the second sphere, however, the differences are a result of statutory solutions that base the model of health care on values that are not uniformly understood. Before 2011, they were conducted and maintained fully, or to a limited extent, from public funds, whereas after 2011 they were maintained from public funds only, when a budgetary unit was selected as an organisational formula of a self-government medical entity. The solutions of the Act of 2011 in its original wording pointed tended to favour commercialisation of the public health sector. The negative side of the solutions adopted is the extraordinary lack of diligence in exercising legislative diligence, especially in the scope of defining the competences and tasks of local self-government units in relation to the medical entities created/ run by these units.